UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MELALUI PROBLEM BASED LEARNING - Ramadhani, Amanda Syahri Nasution, Yulia Sari Harahap (PUSKAPAD, 2022)
Mathematical problem solving ability is one of the abilities that must be possessed by students in solving mathematical problems or problems as well as being possessed by prospective teacher students. So that later students can apply it to students in the field. Based on initial observations by giving tests of mathematical problem solving abilities to students, 26 of 41 students or 46.91% of students scored below 70. Thus, to improve mathematical problem solving skills, the researchers applied a problem based learning model. This research method is Classroom Action Research which consists of 2 cycles. The first cycle discusses flat shapes, and the second cycle discusses spatial shapes. The results of the study in the first cycle of completeness were 73.17% and in the second cycle 87.80%. So that the application of the problem based learning model can improve the mathematical problem solving abilities of semester III-A students of the PGSD Study Program for the 2021-2021 academic year. As for the outputs targeted for the National Certified Journal and National Proceedings and IPR. The results of this study are expected to improve student learning outcomes and students' mathematics learning activities and teachers can apply the numbered head learning model with the help of misyucatung media as a reference for learning models in schools.